Contamination of -percha cones in clinical use by endodontic specialists and general practitioners - Marcia Cristina André Moreira-Nacif; Marilia Fagury Videira Marceliano-Alves; Flavio Rodrigues Ferreira-Alves (Universidad de Antioquia, 2017)
Introduction: the present study evaluated the microbial contamination of gutta-percha cones proceeding from packages used clinically by endodontic specialists and general practitioners. Methods: two gutta-percha cones were selected from 30 original packages, already in clinical use, in dental clinics. The cones were transferred directly to test tubes containing thioglycolate broth and incubated at 37 °C for 21 days in aerobiosis. All tests were done in triplicate. Fractions proceeding from the tubes that presented turbidity were plated in CLED agar and Gram staining. Results: Among the gutta-percha cone boxes tested, 9 (30%) showed bacterial contamination in the tested cones, 4 (13%) of those coming from general practitioners and 5 (17%) coming from specialists. There was no significant difference in the contamination of cones in relation to their origin (p>0,05). Conclusion: The results of the present study reinforce the need for both clinical dentists and endodontics specialists to implement a strict disinfection protocol before using gutta-percha cones, due to the frequency of contamination.